Perbedaan Tingkat Kesadaran Sejarah Siswa Menggunakan Sumber Belajar Situs Banten Lama Dengan Sumber Belajar LKS - Ihya Alfi Azizi; Agus Rustamana; Arif Permana Putra (Universitas Pendidikan Mandalika, 2022)
This study aims to analyze the effects of using Banten Lama learning resources on increasing students' historical awareness and the differences in the historical understanding of students using Banten Lama learning resources and those using LKS learning resources in learning at SMAN 1 Cikeusal. The method was Quasi-Experimental Design with purposive sampling technique sampling (X MIPA 1 experimental class and X MIPA 2 control class). The research instrument used a questionnaire. Then, the data were analyzed using descriptive and inferential statistics. Based on the results of the study, there were differences in the historical awareness of the experimental class students and the control class. The results of the N-Gain showed that the average value of the experimental type was 0.31 in the medium category and the N-Gain of the control class got an average value of 0.13 in the low category. It is concluded that there is an increase in students' historical awareness of learning after using the Old Banten Site as a resource. The t-test t count 2.494 > t table 1.9966 at the 95% confidence level indicated an even more significant difference in the historical awareness of students who use Banten Lama learning resources compared to the use of LKS learning resources.